Seed and seedling morphology of Bauhinia scandens L. - Jeromini, Tatiane Sanches; da Silva, Givanildo Zildo; Martins, Cibele Chalita [UNESP]; Gomes, Francisco Guilhien (Universidade Estadual de Londrina, 2021)
Bauhinia scandens has potential importance as an ornamental and medicinal plant. Researchers have isolated and identified 1-O-alkylglycerol in the leaves of the B. scandens plant, and established antitumor properties using the Brine Shrimp toxicity test, an internationally accepted bioassay. Although this species has high potential, little is known about the viability of seedling production and the morphology of these plants, particularly in terms of seed characteristics and initial stages of germination. The objective of this study was to characterize the seed morphology, germination, and seedlings of B. scandens. Seed water content, weight, and coloration were evaluated. This study also included a description of seed biometrics, external and internal structures, germination, and seedling morphology. Internal seed morphology was evaluated by the anatomical sectioning and X-ray methods. The morphology data obtained were subjected to descriptive statistical analysis and germination data were determined using Cramér's V. B. scandens seeds have a coloration ranging from very dark grayish-red to dark reddish-brown, flat oblong shapes, and rounded bases and apexes with full or slightly undulating margins. Healthy seedlings are produced mainly by seeds with well-formed internal structures. The reddish petiole of the seedling leaves is a taxonomic character for B. scandens identification. The non-domestication and genetic variability of this species reflect on the seed and seedling color and size variation.
Morfologia de semente e plântula de Bauhinia scandens L.
Keywords: Climbing bauhinia; Density; Fabaceae; Internal structure; X-ray